Young Women’s Experiences of Resisting Invitations to Use Illicit Drugs - Koehn, Corinne V.; O'Neill, Linda K. (Canadian Journal of Counselling and Psychotherapy, 2011)
Ten young women were interviewed regarding their experiences of resisting invitations to use illicit drugs. Hermeneutic phenomenology was used to gather and analyze information. One key theme was the motivations that inspired women to refuse drug offers. Young women resisted drug invitations because of their desires to be authentic, protect their futures, reflect a sense of maturity, maintain physical and mental health, and sustain healthy relationships, and because overall they enjoyed life and did not feel the need to alter their emotions and psychological experiences. Implications for prevention programs, counselling and interventions programs, and future research are discussed.